ONOMATOPOEIA IN JAPANESE CULTURAL CONTEXT (Heritage, 2020)
Onomatopoeia is universal in its existence. People naturally translate the sounds they hear into the phonetic vocabulary of their language. In this way, the influences of language and culture are intertwined and the sounds we hear are translated into language. Onomatopoeia is primarily culturally motivated. This complicates the learning of a foreign symbolic system because it requires knowledge of the cultural characteristics of that society as well as a certain degree of understanding of the phonetic system of the language being learned. Gitaigo words, subcategories of onomatopoeia in Japanese, are culturally motivated, but generally words of this category are not formed by real sounds that can be heard, which for a speaker of a foreign language requires great knowledge in the field of Japanese culture.
Keywords: : Onomatopeia, Language, Society, Culture, Japan